White Matter Tract-Cognitive Relationships in Children with High-Functioning Autism Spectrum Disorder - Kato, Yoko (Psychiatry Investig, 2019)
OBJECTIVE: The purpose of the present study was to clarify the relationship between white matter tracts and cognitive symptoms in children with high-functioning autism spectrum disorder (ASD). METHODS: We examined the cognitive functions of 17 children with high-functioning ASD and 18 typically developing (TD) controls and performed diffusion tensor imaging (DTI) tractography. We compared the results between the groups and investigated the correlations between the cognitive scores and DTI parameters within each group. RESULTS: The Comprehension scores in the ASD group exhibited a positive correlation with mean diffusivity (MD) in the forceps minor (F minor). In the TD group, the Comprehension scores were positively correlated with fractional anisotropy (FA) in the right inferior fronto-occipital fasciculus (IFO) and left anterior thalamic radiation (ATR), and negatively correlated with MD in the left ATR, radial diffusivity (RD) in the right IFO, and RD in the left ATR. Additionally, a positive correlation was observed between the Matching Numbers scores and MD in the left uncinate fasciculus and F minor, and RD in the F minor. Furthermore, the Sentence Questions scores exhibited a positive correlation with RD in the right inferior longitudinal fasciculus. Relative to TD controls, the specific tract showing a strong correlation with the cognitive scores was reduced in the ASD group. CONCLUSION: Our findings indicate that white matter tracts connecting specific brain areas may exhibit a weaker relationship with cognitive functions in children with ASD, resulting in less efficient cognitive pathways than those observed in TD children.